Study on Clinical Application of Different Ultrasound-Guided Planar Techniques in Minimally Invasive Percutaneous Nephrolithotomy. (December 2021) - Fan, Difu; Song, Leming; Li, Monong; Luo, Chunxiang; Liao, Xiaohui; Huang, Yongming; He, Xiaolong; Du, Chuance; Liu, Tairong; Michel, Jack; Xie, Donghua
Objective . The objective is to explore the clinical application value of ultrasound long- and short-axis planar technology in real-time guided puncture in minimally invasive percutaneous nephrology. Methods . The clinical data of 80 patients undergoing real-time ultrasound-guided minimally invasive percutaneous nephrolithotomy from September 2018 to October 2019 were analyzed. The patients were randomly divided into 2 groups with different ultrasound-guided puncture techniques, long-axis in-plane technique and short-axis out-of-plane technique. Results . Minimally invasive percutaneous nephrolithotomies under real-time ultrasound guidance were successfully completed in both groups of patients. The success rate of the first puncture in the short-axis out-of-plane group was significantly higher than that in the long-axis in-plane group, and the differences were statistically significant ( P <.05); the total puncture time in the short-axis out-of-plane group was significantly less than the long-axis in-plane group, and the differences were statistical significance ( P <.05); there was no significant difference in the single-stage stone removal rate, total percutaneous renal channels, total hospital stay, and rate of complications by the Clavien classification between the 2 groups ( P > .05). Conclusion . Ultrasound long-axis and short-axis planar technologies can achieve good clinical application results in real-time guided puncture to establish percutaneous renal channels during minimally invasive percutaneous nephrolithotomy. Compared with the long-axis in-plane technique, the short-axis out-of-plane technique can shorten the puncture time and improve the success rate of the first puncture.